Protein Structure and Function Prediction Using I‐TASSER. Issue 1 (17th December 2015) - Yang, Jianyi; Zhang, Yang
Abstract: I‐TASSER is a hierarchical protocol for automated protein structure prediction and structure‐based function annotation. Starting from the amino acid sequence of target proteins, I‐TASSER first generates full‐length atomic structural models from multiple threading alignments and iterative structural assembly simulations followed by atomic‐level structure refinement. The biological functions of the protein, including ligand‐binding sites, enzyme commission number, and gene ontology terms, are then inferred from known protein function databases based on sequence and structure profile comparisons. I‐TASSER is freely available as both an on‐line server and a stand‐alone package. This unit describes how to use the I‐TASSER protocol to generate structure and function prediction and how to interpret the prediction results, as well as alternative approaches for further improving the I‐TASSER modeling quality for distant‐homologous and multi‐domain protein targets. © 2015 by John Wiley & Sons, Inc.